Contribution of miRNAs in the Pathogenesis of Breast Cancer - Soudeh Ghafouri-Fard; Ali Khanbabapour Sasi; Atefe Abak; Hamed Shoorei; Ali Khoshkar; Mohammad Taheri (Frontiers in Oncology, 2021)
Breast cancer is the most frequently diagnosed cancer among females. Gene expression profiling methods have shown the deregulation of several genes in breast cancer samples and have confirmed the heterogeneous nature of breast cancer at the genomic level. microRNAs (miRNAs) are among the recently appreciated contributors in breast carcinogenic processes. These small-sized transcripts have been shown to partake in breast carcinogenesis through modulation of apoptosis, autophagy, and epithelial–mesenchymal transition. Moreover, they can confer resistance to chemotherapy. Based on the contribution of miRNAs in almost all fundamental aspects of breast carcinogenesis, therapeutic intervention with their expression might affect the course of this disorder. Moreover, the presence of miRNAs in the peripheral blood of patients potentiates these transcripts as tools for non-invasive diagnosis of breast cancer.